Multidisciplinary baselines quantify a drastic decline of mussel reefs and reveal an absence of natural recovery. Issue 3 (13th March 2023) - Toone, Trevyn A.; Benjamin, Emilee D.; Hillman, Jenny R.; Handley, Sean; Jeffs, Andrew
Abstract: The onset of the Anthropocene has coincided with enormous global declines in natural ecosystems, leading to losses in the valuable goods and ecosystem services they provide. This global decline, in conjunction with growing recognition of the ecological importance of natural ecosystems, has generated a pressing need for restoration. Effective ecosystem restoration relies on accurate identification of the cause of decline and clear metrics of success, which are only possible with baseline data of both the pre‐degradation and pre‐restoration ecosystems. However, the establishment of these baselines can be difficult as different potential information sources each have benefits and drawbacks. Determining an efficient method to balance these diverse information sources and generate robust baselines is vital to achieving the United Nations' goal of massively scaled‐up ecosystem restoration. Here we expand on the concept of multidisciplinary baselines, or the combined use of sources and methods across a wide disciplinary spectrum to establish comprehensive and reliable ecosystem baselines, and use mussel reefs in the South Island of New Zealand as a test case. Using a combination of comprehensive historical review, extensive shoreline surveys, and local ecological knowledge, we demonstrate that local mussel abundances decreased by 97% since the mid‐1960s as a result of overharvesting, leaving the extant populations scattered, small, and without recovery. This study demonstrates that harnessing multidisciplinary baselines allows for the consolidation of qualitative and quantitative estimates of ecosystem change over hundreds of years, as well as confirmation of causes of ecosystem degradation, and clear documentation of current ecosystem state beyond what is possible from any individual source. This approach to establishing ecosystem baselines also provides valuable avenues for the advancement of restoration by quantifying the temporal and geographic scales of ecosystem decline, identifying areas for intervention, and establishing clear metrics of success.